Utopian Socialist Thought as the Foundation of Marxist Perspective - Govinda Prasad Mainali, (Interdisciplinary Journal of Management and Social Sciences, 2025)
This paper demonstrates that Utopian Socialist Thought serves as the foundation for the scientific socialist theories advanced by the prominent German thinkers Karl Marx and Friedrich Engels. The primary tenets of utopian socialist thought encompass the abolition of private property and the establishment of communal ownership of material goods and productive resources. Key Marxist texts, such as The Communist Manifesto, have prominently articulated the concepts of abolishing private property and establishing common ownership of natural resources and material goods. However, the foundational contributions that introduced these ideas were made by early utopian socialist thinkers, who are often overlooked in these discussions. In discussing the theory of historical dialectical materialism, there is frequent citation of Hegel's Idealism, while the long-standing Utopian Socialist concepts, such as communal ownership of property, are notably excluded. This paper examines the contributions of Utopian Socialist Thought, including the "Testament" of Jean Meslier, the concepts of "Equality Before the Law" and "Equality of Needs" proposed by French thinker Gabriel Bonnot de Mably, Morelly's Code of Nature, and the Babeufism of François Noël Babeuf, asserting their foundational role in the development of Marxist Theory of Scientific Socialist Mode of Production.